Features of dry eye syndrome treatment - E.A. Egorov (РМЖ "Клиническая офтальмология", 2018)
E.A. Egorov Pirogov Russian National Research Medical University, Moscow, Russian Federation Abstract Dry eye syndrome (DES) is a multifactorial disease of eye surface, characterized by a disturbance of tear film homeostasis and accompanied by ophthalmologic symptoms, in development of which an etiological role is played by a disturbance of stability, hyperosmolarity of the tear film, inflammation and damage to the eye surface, and neurosensory changes. In the case of DES, a decrease in secretion of tear fluid leads to an inflammatory reaction in eye tissues and peripheral nerve corruption, which brings to a feeling of dryness and pain in the eye. A triggering mechanism can be both inflammation and oxidative stress, which occurs when a balance between production of active oxygen species and antioxidant defense factors is disturbed. Disturbances at molecular, structural and functional levels of sensitive innervation of the eyeball cause dysesthesia and neuropathic pain in the eye. When selecting the most appropriate DES therapy, one is guided both by a stage of the disease and by peculiarities of symptomatic manifestations in a particular patient. In neurotrophic disorders (after laser surgeries and other conditions) and for reduction of oxidative stress effects, it is recommended to use a tear substitute containing cyanocobalamin (vitamin B12). Cyanocobalamin has an ability to increase antioxidant protection of the eye tissues and helps accelerate corneal reinnervation after laser surgery. Key words: dry eye syndrome, neurosensory disorders, oxidative stress, tear substitutes, cyanocobalamin, sodium hyaluronate. For citation: Egorov E.A. Features of dry eye syndrome treatment. RMJ “Clinical ophthalmology”. 2018;3:146–149.